أهمية مقاييس التدفقات النقدية في اتخاذ القرار الاستثماري في سوق دمشق للأوراق المالية (دراسة تطبيقية) - الغصين, راغب; الموصلي, منال (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يتناول هذا البحث دراسة أهمية المقاييس المشتقة من قائمة التدفقات النقدية في اتخاذ القرار الاستثماري في سوق دمشق للأوراق المالية، كونها إحدى أهم المؤشرات التي يمكن أن يعتمد عليها المستثمرون عند اتخاذهم لقراراتهم الاستثمارية في الأسواق المالية. توصل الباحث في نهاية البحث إلى ما يلي: يؤثر كل من مقياس جودة السيولة المالية، مقياس المرونة المالية والتدفق النقدي الحر تأثيراً معنوياً على قرار المستثمر في سوق دمشق للأوراق المالية. في حين لا يؤثر كل من مقياس جودة الأرباح ومقياس تقييم سياسات التمويل تأثيراً معنوياً على قرار المستثمر في سوق دمشق للأوراق المالية. This research takes into consideration the importance of standards derived from the cash flow statement in making investment decision at Damascus Stock Exchange. This is because they are one of indicators on which the investors can depend when they take their investment decision at financial markets. At the end, the researcher proved that there is significant effect for each of the following standards: liquidity, financial flexibility and free cash flow, on investor decision. On the other hand, there is no significant effect for the following standards: quality of earning and financial policies, on investor decision at Damascus Stock Exchange.